Original paperResults of stent implantation in patients with aortic coarctation - Brzezińska-Rajszys, Grażyna; Zubrzycka, Maria; Jagiełłowicz, Dorota; Kościesza, Andrzej; Książyk, Joanna; Rewers, Bożena; Kansy, Andrzej (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2007)
Background: Stent implantation for coarctation of the aorta has been widely used for the last years. The aim of the study was to analyse the results of stent implantation in patients with native and postoperative coarctation of the aorta performed in The Children’s Memorial Health Institute in Warsaw. Methods: Forty seven patients (pts) with native (33) or postoperative (14 pts) coarctation were treated with stent implantation. Results: Mean patient age was 13.63±3.09 years [range 5-20, median (med.) 14], respectively. The diameter of the coarctation increased from a mean of 5.28±2 mm (range 2-11, med. 5), to 16.19±2.44 mm (range 12-22, med. 16) (p <0.001). Systolic gradient across the coarctation decreased from a mean of 33±12,64 mmHg (range 10-84, med. 30) before to a mean of 3.15±5.21 mmHg (range 0-18, med. 0) after the procedure (p <0.000001). During mean follow-up period of 3.69±2.22 years (range 0.25-9 med. 3) 22 pts (47%) had no antyhypertensive treatment. Mean arterial systolic pressure of 124±13.08 mmHg (range 85-146, med. 125) and diastolic pressure of 66.49±9.68 mmHg (range 40-80, med. 66) were recorded in whole group. Stent redilation was performed in 5 patients during follow up period due to neointimal hyperplasia or patients somatic growth. Covered stents were additionally implanted in 3 pts due to stent fracture and in-stent stenosis, in 1 patient due to small aneurysm detected 4 years after stent implantation, in 1 pt due to aortic arch hypoplasia. Conclusions: Stent implantation in native and postoperative coarctation of the aorta has good immediate and early results. Arterial hypertension therapy can be easily modified after stent implantation. During follow-up period indications for stent redilation and additional covered stent implantation can appear. Key words: coarctation of the aorta, stents, interventional cardiology